The Effect of Job Placement, Compensation, and Job Training on Employee Performance at the Medan Polonia Primary Tax Service Office - Sinaga, Andi; Siregar, Adrian Batara; Agusriza, Agusriza; Sugianto, Andrew; Supriadi, Supriadi; Riana, Zenni (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to determine the effect of work placement, compensation and work training partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama Medan Polonia. The study was conducted at the Kantor Pelayanan Pajak Pratama Medan Polonia Jalan Sukamulia No. 17A Medan, with a population of 111 people, and a study sample. of 53 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24.Based on the analysis results obtained work placement has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Polonia, this is supported by the results of t count analysis > t-table (5,235 > 2,010) at n = 53 at 95% significance level